ANALISIS PEMBELAJARAN MEMBACA MELALUI MEDIA BUKU CERITA BERGAMBAR DI KELAS 2 SD N 1 BEBALANG - Desak Putu Anom Janawati; I Dewa Ayu Ana Ananda (Jurnal Pendidikan Dasar Rare Pustaka, 2026)
Education is the main foundation for the progress of a nation, especially in the development of human resources. Early childhood education (PAUD) is very important because this period is a golden period in children's development. This research focuses on the use of picture storybook media in teaching reading in elementary schools (SD). Picture story books are considered an effective tool in improving children's reading skills, especially in class 2 of SD N 1 Bebalang. This media attracts students' attention through a combination of text and images, makes it easier for them to understand the content of the reading, and provides visual stimuli that support the learning process. Through observations and interviews with students and teachers, it was found that picture story books were able to increase student engagement and understanding in reading. However, there are some challenges in spelling words and the delivery is less fluent for some students. Picture storybooks have positive impacts such as improving literacy skills, but they also have the potential to create dependence on pictures, thereby reducing focus on text. This research shows the importance of appropriate learning media to support the learning process in elementary schools.